Why Is Pollution from US Manufacturing Declining? The Roles of Environmental Regulation, Productivity, and Trade - Shapiro, Joseph S.; Walker, Reed (American Economic Review, 2018)
Between 1990 and 2008, air pollution emissions from US manufacturing fell by 60 percent despite a substantial increase in manufacturing output. We show that these emissions reductions are primarily driven by within-product changes in emissions intensity rather than changes in output or in the composition of products produced. We then develop and estimate a quantitative model linking trade with the environment to better understand the economic forces driving these changes. Our estimates suggest that the implicit pollution tax that manufacturers face doubled between 1990 and 2008. These changes in environmental regulation, rather than changes in productivity and trade, account for most of the emissions reductions. (JEL F18, H23, L60, Q52, Q53, Q56, Q58)